An Optimal Energy Utilization Self Adjusting Variable Speed Drive Scheme for Large Locomotive Drives - Sharaf, Adel M.; El-Gammal, Adel A. A. (Asian Journal of Electrical Sciences, 2012)
The paper presents a novel GA/PSO self regulating diesel driven AC induction motor controlled drive system using the common AC-DC-AC bus interface for industrial applications and electric vehicle EV-locomotion. The proposed control scheme utilizes the dual regulation multi loop error driven controller using the novel modified proportional plus integral plus derivative PID structure with the added error rate compensating auxiliary loop. The EV-drive is fed from the AC-DC-AC interface of a six-pulse controlled rectifier –DC link and six-pulse voltage source inverter VSI using a coordinated dual action control scheme for firing angle control. The diesel engine is controlled to ensure dynamic of power demand with dynamic voltage and current tracking. A dynamic error driven control scheme is proposed to regulate the motor current to limit any inrush currents and overloading conditions, in addition to motor speed dynamic reference tracking. The Proposed tri loop dynamic error driven self regulated-tuned controllers are also utilized to ensure dynamic energy efficiency, control loop decoupling, drive stability and the unified system efficient energy utilization while maintaining accurate speed reference tracking. The paperpresents soft-computing application of both Multi Objective Particle Swarm Optimization (MOPSO) and Genetic search MOGA optimization and search techniques for dynamic online gain-tuning to optimally adjust the settings of the proposed controllers.